2006
DOI: 10.1182/asheducation-2006.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Disease in Acute Lymphoblastic Leukemia: Prophylaxis and Treatment

Abstract: Improved treatment for acute lymphoblastic leukemia (ALL) has virtually eliminated testicular relapse. However, the control of central nervous system (CNS) leukemia remains a therapeutic challenge in childhood ALL, partly because of the late complications arising from cranial irradiation. In most current pediatric protocols, cranial irradiation (12 to 18 Gy) is given to 5% to 25% of patients—those with T-cell ALL, overt CNS disease (CNS3 status) or high-risk cytogenetics. CNS control is a less urgent concern i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 37 publications
2
95
0
2
Order By: Relevance
“…therapy post-HSCT is limited. 4 A recent study involving 1226 adult patients with ALL, AML and CML found a slightly higher rate of CNS relapse after HSCT in the group receiving i.t. therapy.…”
Section: Introductionmentioning
confidence: 98%
“…therapy post-HSCT is limited. 4 A recent study involving 1226 adult patients with ALL, AML and CML found a slightly higher rate of CNS relapse after HSCT in the group receiving i.t. therapy.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have shown significantly higher recurrence rates in patients at risk of CNS relapse, whereas others have been unable to show much of a difference. 1 These results likely reflect differences in patient populations as well as prophylactic strategies. However, there is a paucity of prospective data to truly compare the results of different prophylactic strategies.…”
mentioning
confidence: 87%
“…41,130,161 Factors associated with increased risks for CNS leukemia in children include T-cell immunophenotype, high presenting WBC counts, Ph-positive disease, t(4;11) translocation, and presence of leukemic cells in the CSF. 46 In adults with ALL, CNS leukemia at diagnosis has been associated with a significantly higher risk for CNS relapse in large trials, although no differences were observed in 5-year EFS or DFS rates compared with subgroups without CNS leukemia at presentation. 162,163 CNS leukemia at diagnosis was associated with significantly decreased 5-year OS rate in one trial (29% vs. 38%; P = .03) 162 but not in another trial (35% vs. 31%).…”
Section: Cns Involvement In Allmentioning
confidence: 99%
“…44,45 The observed advantage in outcomes with dexamethasone may, at least partly, be attributed to improved penetration of dexamethasone in the CNS. 46 In a recently published meta-analysis comparing outcomes with dexamethasone versus prednisone in induction regimens for childhood ALL, dexamethasone was associated with a significantly reduced risk for events (i.e., death from any cause, refractory or relapsed leukemia, or second malignancy; risk ratio [RR], 0.80; 95% CI, 0.68-0.94) and CNS relapse (RR, 0.53; 95% CI, 0.44-0.65). 47 However, no advantage was seen with a dexamethasone regarding risk for bone marrow relapse (RR, 0.90; 95% CI, 0.69-1.18) or overall mortality (RR, 0.91; 95% CI, 0.76-1.09), and dexamethasone was associated with a significantly higher risk of mortality during induction therapy (RR, 2.31; 95% CI, 1.46-3.66), neuropsychiatric adverse events (RR, 4.55; 95% CI, 2.…”
mentioning
confidence: 99%